The Bioactivities of Phycocyanobilin from Spirulina - Yi Li (Journal of Immunology Research)
Phycocyanobilin (PCB) is a linear open-chain tetrapyrrole chromophore that captures and senses light and a variety of biological activities, such as anti-oxidation, anti-cancer, and anti-inflammatory. In this paper, the biological activities of PCB are reviewed, and the related mechanism of PCB and its latest application in disease treatment are introduced. PCB can resist oxidation by scavenging free radicals, inhibiting the activity of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase, and delaying the activity of antioxidant enzymes. In addition, PCB can also be used as an excellent anti-inflammatory agent to reduce the proinflammatory factors IL-6 and IFN-γ and to up-regulate the production of anti-inflammatory cytokine IL-10 by inhibiting the inflammatory signal pathways NF-κB and mitogen-activated protein kinase (MAPK). Due to the above biological activities of phycocyanobilin PCB, it is expected to become a new effective drug for treating various diseases, such as COVID-19 complications, atherosclerosis, multiple sclerosis (MS), and ischaemic stroke (IS).